The Evolution of Teaching Resources in South African Schools : A Quest for Adaptive Teaching Strategies - Mzimela, Ayanda; Banoobhai, Mumthaz; Ramollo, Jeanette Khabonina; Mtshali, Thokozani Isaac (Universitas Pendidikan Mandalika, 2024)
This study aims to examine teachers’ usage and perceived value of 40 technology tools in order to enhance student learning outcomes. The study seeks to propose feasible approaches concerning the transition from traditional methods of teaching, towards technology-enhanced teaching in the classroom. This study employed the mixed method approach with embedded mixed methods research design. The data collection techniques were questionnaire, and open-ended questions. Face and content validity was assessed before the administration of the questionnaire. Descriptive statistics were used for quantitative variables. Quantitative data were analyzed by thematic analysis. The results of this study show that only 11% of the teachers are utilizing technology tools in the classroom with learners to support their instructional practices. This study provides valuable insights that will help teachers, principals, and policy makers move toward more technology-enhanced teaching and learning.